Pola Komunikasi Organisasi Dalam Bisnis Warehouses and Distribution Perusahaan Multinasional PT. Maersk Indonesia - Sari, Maduma Yanti; Yazid, Tantri Puspita; Rumyeni, Rumyeni (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
PT. Maersk Indonesia is a multinational company operating in the warehouse and distribution sector. This research aims to determine organizational communication patterns in warehouse and distribution projects. The method used in this research is descriptive qualitative which focuses on observation and interviews. The research results show that the communication patterns developed in the Metalcom project consist of two forms: formal and informal, formal communication in the form of communication from superiors to subordinates, understanding of communication in multinational organizations, especially in Indonesia. communication from subordinates to superiors, horizontal communication, diagonal communication. The communication channel used the Metalcom project's warehousing and distribution using existing technology. Microsoft Teams, email, WhatsApp media. These communication barriers include cultural differences between superiors and subordinates, the use of cultural terminology, native accents or dialects translated into English, and unclear explanations. It is hoped that the results of this research can provide a significant contribution to the